[Mrs. Pál Heim 2]
the front-page of a country newspaper, 1988 girl around the house, children playing, walking in the town&park, bus coach-station, baby in pram, man with motorcycle, 1979 in the Fatra Mountains, nice mountains and view, Martinske Hole, May Day, 1978 Komárom open-air bath, school-leaving ceremony, short piece of bad quality amateur sex-film, military boat & air show, children sport show